Analisis Framing Pemberitaan Demonstrasi Mahasiswa Dongduk Women’s University di Media Kompas.com dan Indozone.id - Ismatul Karimah; Ike Desi Florina; Sarwo Edy (Lembaga Pengembangan Kinerja Dosen, 2025)
Online media play a significant role in shaping public perception through framing processes, particularly on sensitive social issues such as protests. This study aims to analyze and compare how two Indonesian online news platforms, Kompas.com and Indozone.id, framed the student protest at Dongduk Women’s University in South Korea. This research employs a qualitative descriptive approach using Robert N. Entman’s framing model, which includes four elements: defining problems, diagnosing causes, making moral judgments, and suggesting remedies. The data were derived from two news articles published in November 2024. The findings reveal that Kompas.com applied a more critical and comprehensive framing approach, emphasizing social context, historical cases of sexual harassment, and the importance of safe spaces for women. In contrast, Indozone.id focused on the virality aspect, providing minimal analysis and omitting moral and solution-oriented framing. These differences reflect the editorial orientation of each platform and highlight the need for media literacy in an era dominated by algorithm-driven journalism. The study underscores how media framing influences public understanding of gender justice and women's education issues.